Anatomical variant of the extrahepatic bile duct - Chinelli, Javier; Rodríguez, Gustavo (Cirugía del Uruguay, 2020)
The typical or modal arrangement of the bile duct occurs in approximately 60% of the population. Anatomical variants are usually observed at the intrahepatic level, with a frequency of up to 30%.